(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article explores the effective forms of organizing visual arts activities in preschool educational institutions. It emphasizes the role of thematic lessons, play-based approaches, workshops, collaborative projects, project-based learning, digital tools, and culturally responsive methods in fostering creativity, imagination, and combinatorial skills in children. The study highlights how properly structured art activities contribute not only to artistic development but also to cognitive, emotional, and social growth.